Oltre l’Oriente e l’Occidente. l’orientalismo di Tawfīq al-Ḥakīm (Altre Modernità, 2012)
Terms like "East" and "West" are metaphors rather than categories in a technical sense. In particular, the metaphor of "East" has played a decisive role in the development of "orientalistic disciplines" and has also influenced the so-called Eastern populations. The analysis of the literary production of one of the greatest exponents of Egyptian culture in the Twentieth Century - Tawfiq al-Hakim (1898-1987) - will allows us to describe how he modified the vision of the East which was typical of the European Orientalism, beyond the alternative between East and West.
Keywords: Orientalismo; Oriente; Occidente